Tailoring Slurries Using Cosolvents and Li Salt Targeting Practical All‐Solid‐State Batteries Employing Sulfide Solid Electrolytes. Issue 17 (14th March 2021) - Kim, Kyu Tae; Oh, Dae Yang; Jun, Seunggoo; Song, Yong Bae; Kwon, Tae Young; Han, Yoonjae; Jung, Yoon Seok
Abstract: Polymeric binders that can undergo slurry fabrication and minimize the disruption of interfacial Li + contact are imperative for sheet‐type electrodes and solid electrolyte films in practical all‐solid‐state Li batteries (ASLBs). Although dry polymer electrolytes (DPEs) are a plausible alternative, their use is complicated by the severe reactivity of sulfide solid electrolytes and the need to dissolve Li salts. In this study, a new scalable fabrication protocol for a Li + ‐conductive DPE‐type binder, nitrile‐butadiene rubber (NBR)‐LiTFSI, is reported. The less‐polar dibromomethane and more‐polar hexyl butyrate in cosolvents work synergistically to dissolve NBR and LiTFSI, while preserving Li6 PS5 Cl0.5 Br0.5 . It is found that the dispersion of NBR can be controlled by the fraction of the antisolvent (hexyl butyrate), which in turn affects the corresponding performance of the ASLBs. Sheet‐type LiNi0.70 Co0.15 Mn0.15 O2 electrodes tailored using NBR‐LiTFSI outperform those prepared using the conventional insulating binder (NBR) in terms of capacity (163 vs 147 mA h g −1 ) and initial Coulombic efficiency (78.9 vs 70.4%), which is attributed to the facilitated interfacial Li + transport, as confirmed by 6 Li nuclear magnetic resonance and electrochemical measurements. Moreover, NBR‐LiTFSI is functional at 70 ° C and in a graphite anode. Finally, the promising performance of pouch‐type LiNi0.70 Co0.15 Mn0.15 O2 /graphite ASLBs is also demonstrated. Abstract : A new scalable slurry fabrication protocol using a cosolvent targeting dry polymer electrolyte (DPE)‐based binders for all‐solid‐state batteries is developed. Binder dispersion is controlled by adjusting the ratios in the cosolvent, affecting the electrochemical performance. LiNii0.70 Co0.15 Mn0.15 O2 and graphite electrodes tailored from slurries using cosolvents of dibromomethane and hexyl butyrate, targeting the accommodation of DPE and Li6 PS5 Cl0.5 Br0.5, exhibit significantly improved performance.